Democratic Values ​​in Nagari: An Analysis on Electoral System Shifts in One Province of Indonesia - Yarni, Meri; Prasna, Adeb Davega; Yetniwati, Yetniwati; Saputra, Beny (Volksgeist: Jurnal Ilmu Hukum dan Konstitusi, 2024)
The Nagari system, a traditional form of regional government in Minangkabau, has historically employed a direct election method that empowers community members to elect their leaders. This model of participation aligns with the democratic values enshrined stated in the 1945 Constitution and the principles of human rights. However, a 2018 regulation altered this process, transitioning the selection of Nagari leaders from direct community engagement to an indirect election facilitated by the Nagari Traditional Council (KAN). This change was justified as a means to prevent the election of leaders who do not reflect the community’s values. This article seeks to identify the most effective democratic framework for village communities, particularly Nagari societies. The primary issue at hand is the shift from direct democracy to representative democracy in the election of Nagari leaders, instigated by Regional Regulation Number 7 of 2018. Utilizing normative legal research methods, this study emphasizes that the new regulation risks undermining democratic values ​​by restricting direct voter engagement. The findings suggest that these modifications to the electoral process weaken the foundational principles of democracy in Nagari by curtailing direct community participation, a vital aspect of local governance and social cohesion. Therefore, it is essential to reevaluate these regulations to safeguard the democratic rights and participatory traditions of the Nagari community, ensuring alignment with constitutional principles of direct democracy and comprehensive citizen involvement.